Multiple Large Cerebral Infactions in Tuberculous Meningitis: A Rare Case - Kustila, Ela; Dian, Sofiati (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2025)
Cerebral infarction is well known as a consequence arising from tuberculous meningitis (TBM), which generally involves the small and medium-sized intracranial arteries. These infarcts are usually located in regions termed the “TB zone,” perfused by the medial striate and thalamo-perforating arteries, and in the “ischemic zone,” supplied by the lateral striate, anterior choroidal, and thalamogeniculate arteries. In contrast, the involvement of larger arteries is an uncommon feature of tuberculous vasculitis. We report the case of a 24-year-old man with TBM and pulmonary tuberculosis, without HIV infection, who developed loss of consciousness after undergoing a ventriculoperitoneal (VP) shunt procedure. Neuroimaging with computed tomography (CT) revealed extensive cerebral edema accompanied by massive infarctions involving the cerebellum, cerebral hemispheres, and brainstem. These findings illustrate an unusual presentation of multiple large cerebral infarctions associated with TBM. Such extensive infarcts represent severe complications that can be resulted in profound neurological deficits. This case underscores the importance of early recognition and management of TBM-related complications. Prompt initiation of antituberculosis therapy is essential to reduce the risk of fatal outcomes. Moreover, further investigations are warranted to establish more effective therapeutic approach and optimize patient prognosis